Rancang Bangun Alat Penetas Telur Otomatis berbasi Arduino - Anang Sucipto, Muhamad; Bagus Prakoso, Satrio (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2022)
The very rapid population growth in Indonesia has an impact on increasing people's food consumption, especially the needs of poultry and eggs which are rich in important sources of protein. Thus, to meet the availability of food, it must be balanced with adequate supplies so that food security containing high protein is met. The main problem faced is not being able to serve all buyers who have placed an order due to the limited production of chicken seeds. One of the factors is the hatchability of eggs that have not been maximized. The demand for this poultry is growing very rapidly every month along with the number of food stalls and restaurants that offer poultry menus. Necessary in the manufacture of incubators, such as eggs, egg storage methods, temperature and humidity maintenance. Therefore, the researchers made an egg incubator with an automatic controller to simplify the hatching process and get the maximum expected hatching results.